Forecasting Visitors’ behaviour in Crowded Museums - Balzotti, Caterina; Briani, Maya; Corbetta, Alessandro; Cristiani, Emiliano; Minozzi, Marina; Natalini, Roberto; Suriano, Sara; Toschi, Federico (Collective Dynamics, 2020)
In this paper, we tackle the issue of measuring and understanding the visitors’ dynamics in a crowded museum in order to create and calibrate a predictive mathematical model. The model is then used as a tool to manage, control and optimize the fruition of the museum. Our contribution comes with one successful use case, the Galleria Borghese in Rome, Italy.